A New Community Health Center/Academic Medicine Partnership for Medicaid Cost Control, Powered by the Mega Teaching Health Center. (March 2018) - Rieselbach, Richard E.; Epperly, Ted; Friedman, Aaron; Keahey, David; McConnell, Eleanor; Nichols, Karen; Nycz, Greg; Roberts, Jeanette; Schmader, Kenneth; Shin, Peter; Shtasel, Derri
Abstract : Community health centers (CHCs), a principal source of primary care for over 24 million patients, provide high-quality affordable care for medically underserved and lower-income populations in urban and rural communities. The authors propose that CHCs can assume an important role in the quest for health care reform by serving substantially more Medicaid patients. Major expansion of CHCs, powered by mega teaching health centers (THCs) in partnership with regional academic medical centers (AMCs) or teaching hospitals, could increase Medicaid beneficiaries' access to cost-effective care. The authors propose that this CHC expansion could be instrumental in limiting the added cost of Medicaid expansion via the Affordable Care Act (ACA) or subsequent legislation. Nevertheless, expansion cannot succeed without developing this CHC-AMC partnership both (1) to fuel the currently deficient primary care provider workforce pipeline, which now greatly limits expansion of CHCs; and (2) to provide more CHC-affiliated community outreach sites to enhance access to care. The authors describe the current status of Medicaid and CHCs, plus the evolution and vulnerability of current THCs. They also explain multiple features of a mega THC demonstration project designed to test this new paradigm for Medicaid cost control. The authors contend that the demonstration's potential for success in controlling costs could provide help to preserve the viability of current and future expanded state Medicaid programs, despite a potential ultimate decrease in federal funding over time. Thus, the authors believe that the new AMC-CHC partnership paradigm they propose could potentially facilitate bipartisan support for repairing the ACA.